The prevalence of pesticide residues on vegetables offered for sale in the greater Cape Town area - Loubser, M. M. E (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med.)) -- University of Stellenbosch, 1992.